Why students use social networks for education: Extension of UTAUT2 - Ala'a Abu Gharrah; Ali Aljaafreh (OmniaScience, 2021)
Social networks sites have a considerable impact on all our life aspects, especially the educational sector. This study aims at identifying the factors affecting students' actual usage of social networks sites for educational purposes in Jordanian universities.  The proposed model consists factors of UTAUT2 theory (Effort expectancy, Performance expectancy, Social influence, Facilitating condition, Habit, Hedonic motivation). In addition to two added factors (lecturer support, and student-related factors) as an extension. The study was conducted in (6) Jordanian universities, where (381) questionnaires were returned from the study sample with a response rate of (95%) from the total questionnaires that were distributed online. The results showed that (Performance expectancy, Social influence, Effort expectancy, Habit, lecturer support, and student-related factors) have a positive impact on the actual usage of social networks sites for educational purposes in Jordanian universities, while the factors (Facilitating condition and Hedonic motivation) don't support their hypotheses).